"Five-step" laparoscopic lymph node dissection for remnant gastric cancer following Billroth-II gastrectomy: A safe and feasible procedure. (March 2020) - Zheng, Zhi-Fang; Lu, Jun; Zheng, Chao-Hui; Huang, Chang-Ming
Abstract: Background: Laparoscopic surgery (LS) for remnant gastric cancer (RGC) is gaining interest [1–3]. However, due to adhesions to adjacent organs, displacement of anatomical structures, and changes in lymphatic flow triangulation, LS for RGC is considered challenging. In this study, we report our experience performing laparoscopic lymph node dissection for RGC following Billroth-II gastrectomy. Methods: The procedure was separated into five steps: (1) exploration and separation of adhesions and the greater omentum; (2) dissection of the lymph nodes (LNs) in the suprapancreatic area; (3) exposing the right side of the esophagus; (4) exposing the left gastroepiploic vessels and dissection of the LNs in the splenic hilar area; and (5) exposing the left side of the esophagus. The above procedure was performed for 45 RGC patients with stage cT1-4aN0/+ disease from January 2008 to June 2017. Results: There were no conversions to open surgery. The mean operation time was 195.0 ± 52.5 min, the mean blood loss was 104.3 ± 90.4 ml, and the mean times to first flatus, fluid diet, and soft diet were 3.6 ± 1.1 days, 4.5 ± 1.4 days, and 9.0 ± 5.1 days, respectively. A mean of 19.8 ± 12.7 LNs were retrieved. The overall postoperative morbidity rate, major postoperative morbidity [4] rate and mortality rate were 22.2%, 11.1%, and 0%, respectively. At a median follow-up of 47 months, the cumulative 3-year overall survival rate was 56.8%. Conclusions: This novel "five-step" laparoscopic lymph node dissection approach was technically safe and feasible in RGC patients following Billroth-II gastrectomy. Highlights: Laparoscopic surgery for remnant gastric cancer is considered challenging. "Five-step" laparoscopic lymph node dissection for remnant gastric cancer is shown. Video includes the different steps necessary to perform this complex operation.